Comment on “Broken translational and rotational symmetry via charge stripe order in underdoped YBa2Cu3O6+y” - Fine, Boris V. (Science, 2016)
Comin et al. (Reports, 20 March 2015, p. 1335) have interpreted their resonant x-ray scattering experiment as indicating that charge inhomogeneities in the family of high-temperature superconductors YBa2Cu3O6+y (YBCO) have the character of one-dimensional stripes rather than two-dimensional checkerboards. The present Comment shows that one cannot distinguish between stripes and checkerboards on the basis of the above experiment.